2015
DOI: 10.1038/eye.2015.209
|View full text |Cite
|
Sign up to set email alerts
|

South Asian diabetic macular oedema treated with ranibizumab (ADMOR)—real-life experience

Abstract: Purpose Diabetic macular oedema (DMO) is a leading cause for visual impairment in the working age population in the UK. Ranibizumab has been shown to be effective in treatment of DMO in studies based on mainly Caucasian populations. This study reports the 12-month outcome in a cohort of South Asian subjects with DMO treated with ranibizumab. Methods DMO in 51 eyes of 41 South Asian patients was treated with ranibizumab 0.5 mg according to the modified DRCRnet protocol I. Visual acuity (VA) and central macular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…In DME, differences in functional outcomes seem less significant than in nAMD between pivotal and real-life results. The ADMOR real-life study [ 21 ] has investigated the efficacy of ranibizumab in patients with DME in South Asia. The results showed a gain of +8.5 letters at 1 year with a mean number of 7 ± 2 IVI over the first year.…”
Section: Discussionmentioning
confidence: 99%
“…In DME, differences in functional outcomes seem less significant than in nAMD between pivotal and real-life results. The ADMOR real-life study [ 21 ] has investigated the efficacy of ranibizumab in patients with DME in South Asia. The results showed a gain of +8.5 letters at 1 year with a mean number of 7 ± 2 IVI over the first year.…”
Section: Discussionmentioning
confidence: 99%
“…The ADMOR study [19] is the first real-life assessment of the efficacy of ranibizumab in South Asian patients with DME. The mean VA improvement found in the AD-MOR study was comparable to that found in our study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Pro re nata regimen has been commonly used in Turkey in the treatment of DME 10 . Studies from our country have revealed that the real life practice in regards to the visit and injection numbers was far from ideal 10, 11, 12, 13, 14, 15, 1610, 11…”
Section: Introductionmentioning
confidence: 99%